Growth responses in Acacia nilotica inoculated with VAMfungi (Glomus mosseae), Rhizobium sp and Trichoderma harzianum - and R.S. MEHROTRA, PRIYA RANI, ASHOK AGGARWAL (Indian Phytopathology, 2002)
Experiments were conducted to determine the influence of vesicular arbuscular mycorrhizal (VAM) fungi, Rhizobium sp. and Trichoderma harzianum individually as well as in combination on A. nilotica seedlings. G. mosseae was isolated from the rhizosphere of A. nilotica, Rhizobium sp. was isolated from nodules of A. nilotica and T. harzianum was isolated from the rhizoplane of A. nilotica. Co-inoculation of seedlings with G. mosseae and Rhizobium sp. resulted in maximum plant growth and best nodulation.